Diagnostic performance of routine esophagogastroduodenoscopy using magnifying endoscope with narrow‐band imaging for gastric cancer. Issue 1 (23rd August 2017) - Yoshimizu, Shoichi; Yamamoto, Yorimasa; Horiuchi, Yusuke; Omae, Masami; Yoshio, Toshiyuki; Ishiyama, Akiyoshi; Hirasawa, Toshiaki; Tsuchida, Tomohiro; Fujisaki, Junko
Abstract : Background and Aim: In Japan, an increase in the number of routine esophagogastroduodenoscopy procedures is expected because several studies have reported that endoscopy screening has reduced gastric cancer mortality. Magnifying narrow‐band imaging has been reported to be effective for accurate diagnosis of gastric abnormalities such as cancers, adenomas, and intestinal metaplasia. However, the efficacy of this method in routine esophagogastroduodenoscopy has not been clarified. Methods: We divided 3763 patients into two groups. The non‐magnification group included 1842 patients who underwent endoscopy screening using GIF‐H260/LUCERA‐SPECTRUM between October 2014 and February 2015, whereas the magnification group included 1921 patients who underwent screening using GIF‐H290Z/LUCERA‐ELITE between March 2015 and May 2015. In the magnification group, diagnosis of cancer was conducted using the VS classification system. We did not carry out a biopsy when results were confirmed as non‐cancer using magnifying narrow‐band imaging. If cancer was diagnosed, or when a cancer or non‐cancer diagnosis was difficult, we carried out a biopsy. We analyzed and compared the diagnostic performance between the two groups. Results: Gastric biopsy rate was significantly lower in the magnification group (29%) than in the non‐magnification group (41%) ( P < 0.001). Positive predictive value (PPV) for gastric cancer was significantly higher in the magnification group (5.5%) than in the non‐magnification group (2.5%) ( P < 0.001). Furthermore, PPV for gastric epithelial neoplasia was significantly higher in the magnification group (7.9%) than in the non‐magnification group (3.2%) ( P < 0.001). Conclusion: Magnifying narrow‐band imaging improves the diagnostic performance of routine esophagogastroduodenoscopy.